A Systematic Review of Services to DHH Children in Rural and Remote Regions. (5th March 2018) - Barr, Megan; Duncan, Jill; Dally, Kerry
Abstract: Children in regional, rural and remote areas have less access to services than those living in urban areas. Practitioners serving children with a hearing loss have attempted to address this gap, however there are few studies investigating service access and experiences of non-metropolitan families and professionals. This systematic review evaluates the literature on service provision to children with a hearing loss living in regional, rural and remote areas of Australia. A search of five databases, the gray literature and a prominent author located 37 relevant documents. The journal articles were rated for quality and the findings of all documents were themed. The evidence from this review indicates that children with a hearing loss living in regional, rural and remote Australia experience reduced quality and frequency of service. Further investigation is needed to identify the accessibility and suitability of services for children with a hearing loss in non-metropolitan areas.